Konstruksi Tubuh Dalam Novel Mati, Bertahun Yang Lalu Karya Soe Tjen Marching - Valentina Edellwiz Edwar; Muhammad Alfian (Universitas Tidar, 2023)
This study examines the novel Mati, Many Years Ago by Soe Tjen Marching which presents various bodies of postcolonial society subjugated by colonial discourse. The problem of this research is that among these bodies a new body form emerges as a form of resistance. The question of this research is How is the construction of the body in the novel Dead, Many Years Ago? This issue is discussed using Sara Upstone's concept of body and Foucault's body discipline. The research method used is qualitative descriptive. Data was collected through literature studies and note-taking techniques. Data analysis is done by content analysis: data reduction, data classification, and data analysis. The results of the study, namely 1) The body of postcolonial society is subdued through violence that regulates the body through discourse of racism, sexuality, to silencing which leads to death. 2) There is resistance from one body through an ambiguous body, that is, a body that cannot be defined as a living body or a dead body. The condition then caused chaos because it was detached from the colonial discourse that was generally attached to a solid body. The presence of ambiguous bodies provides opportunities for the possibility of re-questioning, criticizing and countering colonial discourse. So that the novel Mati, Many Years Ago can be said to be a representative critique of colonial discourse that still controls former colonies even though they have become independent.